Mycorrhizal types influence island biogeography of plants - Camille S. Delavaux; Patrick Weigelt; Wayne Dawson; Franz Essl; Mark van Kleunen; Christian König; Jan Pergl; Petr Pyšek; Anke Stein; Marten Winter; Amanda Taylor; Peggy A. Schultz; et al. (Communications Biology, 2021)
Delavaux et al. uses global plant databases to examine how the types of mycorrhizal fungi influence the colonization of plants on islands. Their results show that arbuscular mycorrhizal (AM) symbiosis limits plant species’ establishment on islands more than other mycorrhizal associations, and that this initial filter of AM plant species impacts diversification and plant invasion risks.